The Influence of Brand Ambassador, Product Quality, Brand Image, and Healthy Lifestyle in Purchasing Decisions for Lemonilo X NCT Dream Instant Noodle Products - Syah Abadi Mendrofa (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
The purpose of this study is to analyze brand ambassador, product quality, brand image, and healthy lifestyle towards purchasing decisions of lemonilo instant noodle products × NCT Dream in Gunungsitoli city. This research used a quantitative approach. The sample used in this study was 125 respondents using accidental sampling technique in sampling. The data collection technique used in this study was a questionnaire. Data analysis technique using multiple regression analysis. The results of the study show that brand ambassador, product quality, brand image, and healthy lifestyle partially and simultaneously have a positive and significant effect on purchasing decisions of lemonilo instant noodle products × NCT Dream in Gununngsitoli city.